Pengaruh Human Capital dan Organizational Justice Terhadap Kinerja Karyawan Bisnis dan Syariah PT. Bank Sumut Kantor Pusat - Zulkarnaen Zulkarnaen; Kustoro Budiarta (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of Human Capital and Organizational Justice on the performance of Business and Sharia employees at PT. Bank SUMUT Head Office, both partially and simultaneously. The background of this research is based on the importance of human resource quality and the application of Organizational Justice in creating optimal employee performance within a competitive banking environment. This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to 100 employees and analyzed using multiple linear regression tests, t-tests, and F-tests. The results showed that Human Capital has a positive and significant effect on employee performance, indicated by a t-count value of 4.316 > t-table 1.984 with a significance of 0.000 < 0.05. Similarly, Organizational Justice has a positive and significant effect on employee performance with a t-count value of 3.741 > t-table 1.984 and a significance of 0.000 < 0.05. Simultaneously, both variables positively and significantly affect employee performance with an F-count value of 112.022 > F-table 3.09 and a significance of 0.000 < 0.05. These findings indicate that the optimal development of Human Capital and the effective implementation of Organizational Justice can significantly enhance employee performance.